2015
DOI: 10.1038/nature14361
|View full text |Cite
|
Sign up to set email alerts
|

The maternal-age-associated risk of congenital heart disease is modifiable

Abstract: Maternal age is a risk factor for congenital heart disease even in the absence of any chromosomal abnormality in the newborn1-7. Whether the basis of the risk resides with the mother or oocyte is unknown. The impact of maternal age on congenital heart disease can be modeled in mouse pups that harbor a mutation of the cardiac transcription factor gene Nkx2-58. Here, reciprocal ovarian transplants between young and old mothers establish a maternal basis for the age-associated risk. A high-fat diet does not accel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 27 publications
3
65
0
Order By: Relevance
“…Second, the mice in our study voluntarily exercised, likely at lower levels than those in the forced-exercise study. Although we did not control for the exact amounts of exercise each female received, our experimental design was based off of a study that showed moderate voluntary exercise in HFD females was beneficial in the reversal of congenital heart disease in their offspring (Schulkey et al, 2015). Finally, a weak relationship between exercise and weight loss has also been reported in humans (Swift et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Second, the mice in our study voluntarily exercised, likely at lower levels than those in the forced-exercise study. Although we did not control for the exact amounts of exercise each female received, our experimental design was based off of a study that showed moderate voluntary exercise in HFD females was beneficial in the reversal of congenital heart disease in their offspring (Schulkey et al, 2015). Finally, a weak relationship between exercise and weight loss has also been reported in humans (Swift et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This was also the most common diagnosis among the extended pedigrees. We also observed incomplete penetrance, the cause for which is poorly understood but may relate to maternal factors [17]. …”
Section: Discussionmentioning
confidence: 99%
“…To our surprise, the incidence of heart defects in the resulting Nkx2-5 +/− offspring matched that expected for a maternal basis. The offspring of young mothers who ovulated from old ovaries had a low incidence, whereas the offspring of old mothers and young ovaries had a high incidence (Schulkey et al, 2015). An oocyte-based mechanism may contribute to the maternal-age effect in humans, but there is no evidence for one in our mouse model.…”
Section: The Maternal-age Associated Risk Of Congenital Heart Diseasementioning
confidence: 99%
“…The diet had no effect on the incidence of heart defects among the offspring of young mothers, who were markedly hyperglycemic and glucose intolerant. Older mothers developed severe obesity, yet the maternal-age associated risk remained the same (Schulkey et al, 2015). The negative results strongly suggest that the investigation of specific mechanisms one at a time would be risky and inefficient.…”
Section: The Maternal-age Associated Risk Of Congenital Heart Diseasementioning
confidence: 99%
See 1 more Smart Citation